Analisis Pengaruh Current Ratio Dan Debt To Equity Ratio Terhadap Return On Asset Pada PT Nippon Indosari Corpindo Tbk - Cristian Zendrato; Roni Wijaya Zendrato; Dicky Perwira Ompusunggu (Pusat Riset dan Inovasi Nasional, 2023)
The purpose of this study is to review the extent to which the current ratio (CR) and debt-to-equity ratio (DER) have an influence on return on assets (ROA), as well as the effect of both simultaneously on ROA. This study applies a quantitative research design, by collecting secondary data from documentation and literature studies. The purposive sampling method was used to select the research sample. The research findings show that the multiple linear regression coefficient value is Y = 0.004 + 0.003 X1 + 0.066 X2 where the linear regression coefficient of current ratio is 0.003 and the regression coefficient of debt to equity ratio is 0.066 and each increase in financial ratios (CR and DER) by 1% will increase ROA by 0.003% and 0.066%, assuming other variables remain constant. 72.8% or 0.728 is the coefficient of determination. This implies that the independent variables can explain 72.8% of the variation in the value of the dependent variable, with other factors influencing the remaining 27.2%. The debt ratio has a substantially favourable impact on return on assets, while the current ratio partially has no impact.